2019
DOI: 10.3390/en13010129
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Using Markov-Switching GARCH Models in Oil and Natural Gas Trading

Abstract: In this paper, we test the use of Markov-switching (MS) GARCH (MSGARCH) models for trading either oil or natural gas futures. Using weekly data from 7 January 1994 to 31 May 2019, we tested the next trading rule: to invest in the simulated commodity if the investor expects to be in the low-volatility regime at t + 1 or to otherwise hold the risk-free asset. Assumptions for our simulations included the following: (1) we assumed that the investors trade in a homogeneous (Gaussian or t-Student) two regime context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
(125 reference statements)
1
14
0
Order By: Relevance
“…These authors tested this use in U.K. stocks. This use was later developed by several authors [18][19][20][21] in stock markets and other commodity futures such as oil, natural gas, corn, or soybean [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These authors tested this use in U.K. stocks. This use was later developed by several authors [18][19][20][21] in stock markets and other commodity futures such as oil, natural gas, corn, or soybean [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…With these forecasted probabilities, the trader or portfolio manager could follow a trading algorithm similar to the one of Brooks and Persand [17] or the one tested by De la Torre-Torres, Galeana-Figueroa, and Álvarez-García [20,22] or De la Torre-Torres et al [23]:…”
Section: The Rationale Behind Ms and Ms-garch Models The Input Data Processing Method And The Trading Strategy Simulation's Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…For the specific case of trading decisions in energy futures, we found the work of De la Torre-Torres, Galeana-Figueroa and Álvarez-García [83] who tested the use of MS and MS-GARCH models in the Oil and Natural gas markets. By using the 1-month contract weekly historic data of each commodity future, the authors simulated a portfolio that used the aforementioned investment strategy from June 1998 to February 2019 and found that only the use of a Gaussian MS model leads to an overperformance in the oil market.…”
Section: Literature Reviewmentioning
confidence: 99%